Effect of Vessel Size on Shoreline and Shore Structure Damage Along the Great Lakes Connecting Channels. - Wuebben,J L (1983)
In conjunction with the Great Lakes connecting channels and harbors study, this report examines the potential damage to the shore and shore structures due to an increase in vessel size. The areas considered in this report are the United States shorelines along the St. Marys, St. Clair and Detroit rivers. The potential for shoreline or shore structure damage due to an increase in vessel size was reviewed on both a conceptual and site-specific basis. Ship-induced waves were ruled out as a damage mechanism since the analysis showed that the contemplated increases in vessel size would not significantly affect wave heights in the nearshore zone. Propeller wash was discounted for similar reasons. Ship-induced drawdown was determined to be the major potential damage mechanism. While larger ships potentially produce more damage, this potential is significant only in severely restricted channel sections for the size increase considered here. By far the most significant factor in ship-related damage potential is vessel speed. In almost all areas, the effect of an increase in vessel size could be eliminated by a reduction in vessel speed of 1-2 mph. (Author)